2016
DOI: 10.12783/issn.1544-8053/13/s1/27
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Two kinds of Herbage Crops on the Removal of High Molecular Weight Polycyclic Aromatic Hydrocarbons in Sludge

Abstract: ABSTRACT:The purpose of this study was to compare the effects of two herbage crops (awnless brome and alfalfa) on the removal of high molecular weight polycyclic aromatic hydrocarbons (HMW-PAHs) in sludge, including 9 PAHs. The results showed that Awnless brome and alfalfa had similar removal percentages for the total Σ9 HMWPAHs in the sludge, which were 85.75% and 85.08%, respectively. However, these two plants were different in the removal percentages of individual PAHs, for example, awnless brome had higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…This suggested that there is a need for improvement in the bioremediation of PAHs in soil. Some of the selected plants such as Zea mays L., Trifolium repens , Lolium perenne L. ( Xu et al, 2006 ), Apium graveolens , Raphanus sativus , Solanum tuberosum , Daucus carota ( Yi and Crowley, 2007 ), Medicago sativa L., Bromus inermis ( Sheng-Dong et al, 2016 ), flowering plant Helianthus annuus L. ( Tejeda-Agredano et al, 2013 ), and Hippophae rhamnoides L. ( Shevchyk and Romaniuk, 2016 ) had been reported for bioremediation of pyrene-contaminated soil. Plant roots enhance bacterial density and increase the surface contact between microorganisms and pollutants, leading to the promotion of degradation in the rhizospheric soil ( Henner et al, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…This suggested that there is a need for improvement in the bioremediation of PAHs in soil. Some of the selected plants such as Zea mays L., Trifolium repens , Lolium perenne L. ( Xu et al, 2006 ), Apium graveolens , Raphanus sativus , Solanum tuberosum , Daucus carota ( Yi and Crowley, 2007 ), Medicago sativa L., Bromus inermis ( Sheng-Dong et al, 2016 ), flowering plant Helianthus annuus L. ( Tejeda-Agredano et al, 2013 ), and Hippophae rhamnoides L. ( Shevchyk and Romaniuk, 2016 ) had been reported for bioremediation of pyrene-contaminated soil. Plant roots enhance bacterial density and increase the surface contact between microorganisms and pollutants, leading to the promotion of degradation in the rhizospheric soil ( Henner et al, 1997 ).…”
Section: Introductionmentioning
confidence: 99%